Pengaruh Good Corporate Governance, Kinerja Keuangan dan Retention Ratio terhadap Harga Saham - Budiantini, Alya (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2024)
Good Corporate Governance (GCG), Financial Performance, and Retention Ratio are essential factors that can influence stock prices. Good GCG can enhance investor confidence and drive positive financial performance. Strong financial performance can increase the company's value and attract investors to buy the company's shares. A high Retention Ratio indicates that the company can retain quality employees, which can enhance productivity and profitability. This research aims to analyze the influence of GCG, Financial Performance, and Retention Ratio on Stock Prices. The method employed is quantitative. The population used in this study is the LQ45 companies listed on the Indonesia Stock Exchange for the period 2017-2021, totaling 45 companies, and the sample criteria selected 17 companies. Data analysis utilizes descriptive statistics, panel data regression model estimation, classical assumption tests, hypothesis testing, and MRA using Eviews 12. The results indicate a significant influence of the Retention Ratio on Stock Prices, with the statistically higher t-value compared to the t-table (2.663118 > 1.99006). However, variables such as the Board of Directors, Independent Commissioners, Return on Assets (ROA), and Earning Per Share (EPS) do not demonstrate a significant influence on Stock Prices as their t-values are lower than the critical t-value (t-value < 1.99006). The correlation results show that 88.3% of the variation in Stock Prices can be explained by the independent factors examined in this study, while the remaining 11.7% may be influenced by other unmodeled factors. These findings provide valuable insights into understanding the factors affecting company stock prices and underscore the importance of profit retention in the context of a company's market value.